Global volatile profile of virgin olive oils flavoured by aromatic/medicinal plants. (15th July 2017) - Perestrelo, R.; Silva, C.; Silva, P.; Câmara, J.S.
Highlights: Establishment of global volatile signature of virgin and flavoured olive oils. LLME/GC–qMS revealed better performance on VOCs extraction than HS-SPME/GC–qMS method. Up to 60 VOCs were identified in commercial virgin and flavoured olive oils. PCA allowed to distinguish virgin from flavoured olive oils. Results used to produce high quality olive oils and increase its valorization. Abstract: The global volatile profile of commercial virgin olive oils and flavoured olive oils with aromatic/medicinal plants, was established using liquid-liquid microextraction (LLME) and headspace solid-phase microextraction (HS-SPME) combined with gas chromatography–quadrupole mass spectrometry (GC–qMS). More than 60 volatile organic compounds (VOCs belonging to different groups were identified using both methods. Olive oils volatile profile was slightly influenced by maceration process, which occurred at room temperature (20 ± 2 °C) for 15 days. The predominant differences were observed in terpenoids group, since some of them were only identified in the flavoured olive oils, while others showed an increase with the maceration process. VOCs mass transfer from plants to olive oils could explain the observed results. Principal components analysis (PCA) applied to LLME/GC–qMS data allowed to distinguish the olive oils. The flavoured oils would increase the use of olive oil among consumers as consequence of the improvement of its aromatic profile and healthy properties.